The Influence of Group Guidance on Student Discipline at SMA Negeri 2 Tarakan - Ita Cahya Anameswari; Cici Ismuniar; Siti Rahmi (Asha Publishing, 2025)
Discipline is the key to success, so if someone has undisciplined behavior, it will have a negative impact on themselves and others because it can distance them from success. The objective of this research is to investigate the impact of group guidance on students' disciplinary behavior at SMA Negeri 2 Tarakan. This study adopts a quantitative approach through a pre-experimental method, utilizing a one-group pretest-posttest design to assess changes before and after the intervention. The data collection technique in this study was a questionnaire. Student discipline is reviewed from 3 aspects, namely: 1) order; 2) ability to control oneself; and 3) ability to concentrate. The population of this study was 451 grade XI students at SMA Negeri 2 Tarakan. The sample in this study consisted of 12 students, selected through a simple random sampling technique. Data were analyzed using both descriptive and inferential statistical methods, with the assistance of SPSS version 25 software. The results of the study indicate that during the pretest phase, students' discipline levels were categorized as high and very high, with an average score of 156.7. Following the implementation of the posttest, the average score increased to 175.3, remaining within the very high category. Hypothesis testing using a paired sample t-test (parametric) revealed a significance value of 0.000, which is less than 0.05. This result leads to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (Ho), indicating that group guidance has a significant effect on student discipline at SMA Negeri 2 Tarakan.